2017
DOI: 10.1523/jneurosci.0093-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Time-Varying Cochlear Implant Stimulation in Auditory Cortex of Awake Marmosets (Callithrix jacchus)

Abstract: Electrical stimulation of the auditory periphery organ by cochlear implant (CI) generates highly synchronized inputs to the auditory system. It has long been thought such inputs would lead to highly synchronized neural firing along the ascending auditory pathway. However, neurophysiological studies with hearing animals have shown that the central auditory system progressively converts temporal representations of time-varying sounds to firing rate-based representations. It is not clear whether this coding princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This was also the case for temporally modulated electrical and acoustic stimuli. Single-unit recordings revealed that cochlear implant electrical stimulation produced both stimulus-synchronized and nonsynchronized firing, with individual units responding similarly to acoustic and electrical stimulation [40].…”
Section: Adaptive Plasticitymentioning
confidence: 99%
“…This was also the case for temporally modulated electrical and acoustic stimuli. Single-unit recordings revealed that cochlear implant electrical stimulation produced both stimulus-synchronized and nonsynchronized firing, with individual units responding similarly to acoustic and electrical stimulation [40].…”
Section: Adaptive Plasticitymentioning
confidence: 99%
“…A final limitation to consider is a general one concerning the use of vocoder simulations in normalhearing listeners with acoustic stimuli. Although some early studies in anesthetized animals showed broad activation of auditory cortex from electrical stimulation of the cochlea via a CI (Raggio and Schreiner 1999;Bierer and Middlebrooks 2002), in line with expectations from comparisons of acoustic simulations of CI stimulation in humans (e.g., Oxenham and Kreft 2014;O'Neill et al 2019), recent studies with awake marmosets have reported that CI stimulation led to much less auditory cortical activation than comparable acoustic stimulation (Johnson et al 2016(Johnson et al , 2017. Such differences may in part reflect the poor spectral resolution provided by the CI, but it may also indicate more fundamental differences in the response of the auditory system to electrical stimulation, which would not be captured via a vocoder simulation.…”
Section: Limitations and Future Directionsmentioning
confidence: 55%
“…Here we identified the Gabor atom (Gabor, 1947), also known as the Gaussian-enveloped tone (GET), as a means of simulating the three features of modern CI processing. The GET has been used to study a wide range of auditory phenomena including interaural timing difference using temporal envelope cues (Buell and Hafter, 1988; Bernstein and Trahiotis, 2002), intensity discrimination (van Schijndel et al ., 1999), and cortical encoding of acoustic and electric pulsatile stimulation (Johnson et al, 2017). Because Gaussian envelope is preserved in both time and frequency domains, the GET can be used to simulate and control accurately the discrete pulses and their current spread, producing reasonable CI simulation in binaural masking release and binaural image (Lu et al ., 2007; Lu et al ., 2010; Goupell et al ., 2013; Kan et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here we identified the Gabor atom (Gabor, 1947), also known as the Gaussian-enveloped tone (GET), as a means of simulating the essential features of modern CI processing as discussed above. The GET has been used to study a wide range of auditory phenomena in normal hearing or hearing-impaired listeners, e.g., temporal gap detection (Schneider et al, 1994; Trehub et al, 1995), intensity discrimination (Baer et al, 1999; van Schijndel et al, 1999; Baer et al, 2001; Nizami et al, 2001), simultaneous and non-simultaneous masking (Laback et al, 2011; Laback et al, 2013), interaural timing difference (ITD) (Buell and Hafter, 1988), and cortical encoding of pulsatile stimulation (Lu and Wang, 2000; Lu et al, 2001; Johnson et al, 2017). More recently, GET train has been used to simulate some basic tasks on binaural hearing with CIs, e.g., sound localization (Goupell et al, 2010; Jones et al, 2014), lateralization (Ehlers et al, 2016), binaural masking level differences (Lu et al, 2010), temporal weighting of ITD and interaural level difference (ILD) (Brown and Stecker, 2010), effects of electrode place mismatch on binaural cues (Goupell et al, 2013; Kan et al, 2013), and effects of temporal quantization on ITD discrimination (Dieudonne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%